Comparison between anthropometry and multi-frequency bioimpedance for body composition evaluation in Brazilian elite U-20 soccer athletes - Herdy, Carlos Vinicius (2020)
Young soccer players undertake anthropometric measurements for directing the effectiveness of training programs. However, the use of the eight-electrode electrical bioimpedance method is increasingly being used for the body composition evaluation. The purpose of this study was to compare and correlate body composition, using anthropometric predictive equations, with the use of electrical bioimpedance. Thirty Brazilian high-performance men, players of the U-20 category, participated in the study, while their position in the field was recorded. Anthropometrics were assessed using the predictive equations of Faulkner, Yuhasz, Carter, and Slaughter and electrical bioimpedance. There were no significant differences between methods for anthropometric evaluation, while traditional body composition analysis and bioimpedance showed moderate correlations with respect to the anthropometric protocols, Faulkner (r = 0.63, p<0.01), Yuhasz (r = 0.64, p<0.01), Carter (r = 0.64, p<0.01) and Slaughter (r = 0.53, p<0.01). According to the present investigation, bioimpedance with eight electrodes can be a reliable tool for the assessment of body composition in young soccer players.